2010
DOI: 10.1093/carcin/bgq263
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor gene variants and risk of endometrial cancer

Abstract: Prolonged excessive estrogen exposure unopposed by progesterone is widely accepted to be a risk factor for endometrial cancer development. The physiological function of progesterone is dependent upon the presence of its receptor [progesterone receptor (PGR)] and several studies have reported single nucleotide polymorphisms (SNPs) in the PGR gene to be associated with endometrial cancer risk. We sought to confirm the associations with endometrial cancer risk previously reported for four different PGR polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The Alu insertion has been shown to reduce transcript stability, and the amino acid substitution (V660L) to result in lower efficiency in opposing proliferation of cells expressing the A isoform of the receptor [14], the main isoform mediating the anti-proliferative effects of progesterone in the endometrium [42]. The suggestive increase in risk we observed with PGR rs1042838 is consistent with these observations, as well as with results of some [6, 16, 25], but not all [26, 43, 44], other epidemiologic studies. The large study conducted by Lee et al, which examined 17 haplotype-tagging SNPs in the PGR gene, reported that the PROGINS allele, and haplotypes containing the PROGINS allele, were associated with increased endometrial cancer risk [25].…”
Section: Discussionsupporting
confidence: 86%
“…The Alu insertion has been shown to reduce transcript stability, and the amino acid substitution (V660L) to result in lower efficiency in opposing proliferation of cells expressing the A isoform of the receptor [14], the main isoform mediating the anti-proliferative effects of progesterone in the endometrium [42]. The suggestive increase in risk we observed with PGR rs1042838 is consistent with these observations, as well as with results of some [6, 16, 25], but not all [26, 43, 44], other epidemiologic studies. The large study conducted by Lee et al, which examined 17 haplotype-tagging SNPs in the PGR gene, reported that the PROGINS allele, and haplotypes containing the PROGINS allele, were associated with increased endometrial cancer risk [25].…”
Section: Discussionsupporting
confidence: 86%
“…Over the past 10 years, a number of studies have reported that certain genetic variants are associated with endometrial cancer risk, including polymorphisms in genes involved in estrogen metabolism (3). However, very few of these associations have been confirmed (47). Given that almost all previous studies used the candidate-gene approach, in which only a limited number of genetic variants are investigated, and the choice of genes is driven by our limited knowledge of cancer biology, more comprehensive genetic investigations of endometrial cancer risk are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen studies met the inclusion criteria, the characteristics of which are reported in Table 1. Of these 19 studies, 10 were breast cancer (BC) studies in which all of the patients were of European ethnicity [11], [16]–[24]; six were ovarian cancer (OC) studies that only included patients of European origin [10], [17], [20], [25], [26], [27] and three studies were endometrial cancer (EC) studies, which enrolled patients of different ethnic groups [28], [29], [30].…”
Section: Resultsmentioning
confidence: 99%